Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum dan Belanja Modal terhadap Ketimpangan Distribusi Pendapatan - Putri, Ni Putu Valentiana Shanty; Suardhika Natha, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Characteristic difference of each region has a strong influence in creating an uniquality economic growth. In which causes some regions grow fast, while others are slower. This will then causing an uniquality in both to the development and the income among the regions. The fiscal decentralization is needed to decrease the differences by managing back the financial recourses in each region.  This research is aimed to find out simultaneously and partially the influence of the local revenue, general allocation fund, the capital expenditure to the income differences among the districts / cities in Bali. The data resources that are used are secondary data and pooled data. The analysis technique of the data that is used is multiple linear regression analysis. The results of the analysis show that simultaneously the   local revenue, general allocation fund, the capital expenditure have a significant influence to the difference of the income. Partially, the local revenue and general allocation fund have positive and significant influence to the difference of the income whereas the capital expenditure has a negative and significant influence to the difference of the income.
Keywords: Local Revenue; General Allocation Fund; Capital Expenditure; Income distribution Differences